Coordination supramolecular action driven Y-type non-fullerene receptor electron transport material as well as preparation method and application thereof
The Y-type non-fullerene acceptor material driven by coordination supramolecular action has been ordered assembled in perovskite solar cells, solving the interface problem between the fullerene electron transport layer and the perovskite active layer, and significantly improving the efficiency and stability of the solar cell.
Patent Information
- Application Number
- CN202510061863.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-15
AI Technical Summary
In existing trans perovskite solar cells, the chemical effect between the fullerene electron transport layer and the perovskite active layer is weak, the energy state structure matches low, and the molecules are disordered, which limits its efficiency and stability.
Using the Y-type non-fullerene acceptor material driven by coordination supramolecular action, the introduction of orthophylline and crown ether groups promotes the orderly assembly of Y-type molecules on the perovskite surface, optimizes the interface energy arrangement and efficient charge transport.
The laboratory power conversion efficiency and certified power conversion efficiency of perovskite solar cells are improved, and the stability and carrier dynamics of the device are significantly improved, with an attenuation rate of less than 10%.
Smart Images

Figure CN119874720A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of perovskite photovoltaic materials, and specifically relates to a Y-type non-fullerene acceptor electron transport material driven by a coordinated supramolecular action, and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Trans-perovskite photovoltaic technology has attracted widespread attention due to its negligible hysteresis effect and high matching degree in stacked cells, and has gradually shown great potential in terms of efficiency and stability. With the continuous optimization of the light-absorbing layer of organic-inorganic hybrid perovskite thin films, the factors limiting the improvement of the efficiency and stability of trans-perovskite solar cells have been mainly concentrated on the interface, especially the interface between the perovskite layer and the charge transport layer, and the interface between the transport layer and the electrode. These interface problems mainly include interface defects between the active layer and the transport layer, severe material diffusion and ion migration, and interface energy level mismatch.
[0004] At present, the electron transport layer of trans-perovskite mainly uses fullerene C60, but there are problems such as weak chemical reaction between fullerene and perovskite, low energy state structure matching between fullerene electron transport layer and perovskite active layer, and molecular disorder inside fullerene electron transport layer. Developing new electron transport materials to replace fullerene materials is the best choice to fundamentally overcome these problems. Conventional Y-type non-fullerenes have the characteristics of high mobility and adjustable energy levels, and have the potential to replace fullerene materials. However, the intermolecular interaction between conventional Y-type non-fullerene acceptors and perovskites is dispersed, resulting in disordered interface energy, which limits its potential to replace fullerenes. The introduction of coordinated supramolecular action groups can drive the orderly assembly and arrangement of Y-type molecules at the interface, which is an effective way to overcome the above problems. Summary of the invention
[0005] In order to solve the problems in the prior art, the present invention provides a Y-type non-fullerene acceptor electron transport material driven by a coordinated supramolecular effect, and a preparation method and application thereof.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] In a first aspect, the present invention provides a Y-type receptor material having a structure shown in any one of Formulas I to II:
[0008]
[0009] Among them, R 1 , R2 W, X, Y, and Z are independently one of C6-C50 straight-chain or branched-chain alkyl groups; and W, X, Y, and Z are independently one of hydrogen, fluorine, chlorine, bromine, and iodine.
[0010] Furthermore, R 1 , R 2 Each of the following is independently selected from a C6 to C20 straight chain or branched chain alkyl group.
[0011] Furthermore, the receptor material is selected from one of the following structures:
[0012]
[0013] In a second aspect, the present invention provides a method for preparing the above-mentioned Y-type receptor material, wherein the synthesis of the structure of formula I comprises the following steps:
[0014] (1) Compound M1 and LiAlH 4 The reaction yields intermediate M2;
[0015] (2) intermediate M2 reacts with 1,10-phenanthroline-5,6-dione to obtain intermediate M3;
[0016] (3) Intermediate M3, DMF, POCl 3 The reaction yields intermediate M4;
[0017] (4) intermediate M4 reacts with the terminal group of IC to obtain a structure shown in formula I;
[0018] The reaction process is:
[0019]
[0020] Among them, R 1 , R 2 W, X, Y, and Z are independently one of C6-C50 straight-chain or branched-chain alkyl groups; and W, X, Y, and Z are independently one of hydrogen, fluorine, chlorine, bromine, and iodine.
[0021] Further, in step (1), specifically: the Y intermediate core M1 is dissolved in ultra-dry solvent tetrahydrofuran, and added into a double-mouth round-bottom bottle under nitrogen protection, and then the reducing agent LiAlH is added. 4 The tetrahydrofuran solution was stirred for 5 to 10 minutes, and then refluxed in an oil bath for 12 hours. The heating was stopped, and the ice bath was cooled to 0°C. An equal volume of water to tetrahydrofuran was slowly added to the reaction system, and the mixture was stirred evenly and extracted with ethyl acetate. The organic phase was dried over anhydrous sodium sulfate for 2 to 5 hours. The solvent was removed by rotary evaporation, and the obtained intermediate M2 was used directly in the next step without purification;
[0022] Further, in step (1), M1 and LiAlH 4The molar ratio is 7 to 10:1.
[0023] Further, in step (2), specifically: M2 is dissolved in a mixed solvent of anhydrous ethanol and acetic acid in a volume ratio of 1:1, and 1,10-phenanthroline-5.6-dione is added. The reaction is carried out at 100°C for 8 to 10 hours. After cooling to room temperature, the mixture is extracted with water and ethyl acetate. The organic phase is dried over anhydrous sodium sulfate for 2 to 5 hours. The solvent is removed by rotary evaporation, and the crude product is purified by column chromatography to obtain the intermediate M3.
[0024] Furthermore, in step (2), the molar ratio of M2 to 1,10-phenanthroline-5,6-dione is 1:1-2.
[0025] Further, in step (3), specifically: under nitrogen protection, M3 was dissolved in 1,2-dichloroethane and cooled to 0°C, stirred for 20 minutes, and then DMF and POCl were added. 3 . Reflux reaction for 12 hours. Then cool to room temperature, add sodium acetate aqueous solution, and continue stirring for 1 hour. The reaction system is extracted with dichloromethane, and the organic phase is dried with anhydrous sodium sulfate for 2 to 5 hours. The crude product is subjected to column chromatography to obtain intermediate M4.
[0026] Further, in step (3), DMF and POCl are added 3 , M3, DMF and POCl 3 The ratio is 0.157mmol:0.1~1mL:1~3mmol.
[0027] Further, in step (4), specifically: dissolving M4 and IC terminal raw materials in toluene. Then adding BF 3 ·OEt 2 and acetic anhydride, react with stirring at room temperature for 30 to 45 minutes, add methanol dropwise while stirring the reaction solution to obtain a large amount of black precipitated solid, that is, to obtain a compound having the structure shown in formula I.
[0028] Furthermore, in step (4), the molar ratio of M4 to IC end group is 1:2.2-3.
[0029] Furthermore, in step (4), BF 3 ·OEt 2 The volume ratio of acetic anhydride to acetic anhydride is 2.5 to 3.5:1, preferably 3:1.
[0030] The synthesis of the structure of formula II comprises the following steps:
[0031] (1) Compounds M7 and M8 react to obtain intermediate M9;
[0032] (2) Intermediate M9, DMF, POCl 3 The reaction yielded intermediate M10;
[0033] (3) The intermediate M10 reacts with the IC terminal group to obtain a structure as shown in Formula II;
[0034] The reaction process is:
[0035]
[0036] Among them, R 1 , R 2 W, X, Y, and Z are independently one of C6-C50 straight-chain or branched-chain alkyl groups; and W, X, Y, and Z are independently one of hydrogen, fluorine, chlorine, bromine, and iodine.
[0037] Further, in step (1), specifically: M7 is dissolved in anhydrous ethanol, and then M8 is added, and the reaction is carried out at 110°C for 8 to 10 hours. Then the reaction is cooled to room temperature. The reaction is extracted with water and ethyl acetate. The organic phase is dried over anhydrous sodium sulfate. The solvent is removed by rotary evaporation, and the crude product is subjected to column chromatography to obtain the M9 intermediate.
[0038] Furthermore, in step (1), the molar ratio of M7 to M8 is 1:1 to 1.2.
[0039] Further, in step (2), specifically: under nitrogen protection, M9 was dissolved in 1,2-dichloroethane and cooled to 0°C, stirred for 20 minutes, and then DMF and POCl were added. 3 . Reflux reaction for 12 hours. Then cool to room temperature, add sodium acetate aqueous solution, and continue stirring for 1 hour. The reaction system is extracted with dichloromethane, and the organic phase is dried with anhydrous sodium sulfate for 2 to 5 hours. The crude product is subjected to column chromatography to obtain intermediate M10.
[0040] Further, in step (3), M9, DMF and POCl 3 The ratio is 0.157mmol:0.1~1mL:1~3mmol.
[0041] Further, in step (4), specifically: dissolve M10 and IC terminal raw materials in toluene. Then add BF 3 ·OEt 2 and acetic anhydride, react at room temperature with stirring for 30 to 45 minutes, and add methanol dropwise while stirring the reaction solution to obtain a large amount of black precipitated solid, i.e., a compound having the structure shown in Formula II.
[0042] Furthermore, in step (4), the molar ratio of M10 to IC end group is 1:2.2-3.
[0043] Furthermore, in step (4), BF 3 ·OEt 2 The volume ratio of acetic anhydride to acetic anhydride is 2.5 to 3.5:1, preferably 3:1.
[0044] In a third aspect, the present invention provides the use of the above-mentioned Y-type acceptor material in the preparation of perovskite solar cells.
[0045] In a fourth aspect, the present invention provides a perovskite solar cell, comprising a substrate, a bottom electrode, a hole transport layer, a perovskite photovoltaic active layer, an electron transport layer, and a top electrode;
[0046] Wherein, the electron transport layer includes the above-mentioned Y-type acceptor material.
[0047] In a fifth aspect, the present invention provides a method for preparing the above-mentioned perovskite solar cell, comprising sequentially arranging the bottom electrode, hole transport layer, perovskite photovoltaic active layer, electron transport layer, and top electrode on a substrate.
[0048] Furthermore, the preparation method includes: providing a substrate; forming a bottom electrode layer on one surface of the substrate, forming a hole transport layer on the side of the bottom electrode layer facing away from the substrate, forming a perovskite photovoltaic active layer on the side of the hole transport layer facing away from the substrate, and forming an electron transport layer on the side of the perovskite photovoltaic active layer facing away from the substrate.
[0049] Furthermore, in the electron transport layer, the Y-type acceptor material is dissolved in a solvent and spin-coated on the perovskite photovoltaic active layer, and the concentration of the Y-type acceptor material is 2 to 20 mg / mL, preferably 10 mg / mL.
[0050] The beneficial effects of the technical solution of the present invention are mainly reflected in:
[0051] Currently, fullerene derivatives are widely used as efficient electron transport layers (ETLs) in pin perovskite photovoltaics, but face challenges in mitigating interfacial recombination losses and ensuring stable film morphology. Non-fullerene acceptors (NFAs), commonly used in organic photovoltaics, are a promising alternative to fullerene-based electron transport materials. However, the suboptimal performance of NFAs-based perovskite photovoltaics requires customization through molecular engineering. Based on this, the present invention uses o-phenanthroline and crown ethers with coordinated supramolecular properties to replace the benzothiadiazole core of Y6 and develops two Y-type NFAs, Y-Phen and Y-CE. These modifications promote the orderly assembly of molecules on the perovskite surface through supramolecular interactions, thereby optimizing the interfacial energy arrangement, promoting efficient charge transport, improving molecular stacking, and effectively improving carrier dynamics. Using Y-Phen and Y-CE as ETLs for perovskite solar cells, respectively, can obtain laboratory power conversion efficiencies of 25.03% and 25.61%, among which the device using Y-CE as ETL achieved a certified power conversion efficiency of 25.59%. These results are significantly higher than the power conversion efficiency of the device when Y6 is used as ETL (23.58%). In addition, the degradation rate of PCE of the optimized device is less than 10% after 1440 hours. It has excellent performance in the preparation of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0053] Figure 1 is the H NMR spectrum of the Y-Phen molecule in Example 1 of the present invention;
[0054] Figure 2 is the H NMR spectrum of the Y-CE molecule in Example 1 of the present invention;
[0055] Figure 3 Thermogravimetric analysis spectra of Y-Phen, Y-CE and comparative molecule Y6 in Example 1 of the present invention;
[0056] Figure 4 are the UV-visible-near infrared absorption curves of Y-Phen, Y-CE and comparative molecule Y6 in Example 1 of the present invention;
[0057] Figure 5 The electron mobility analysis curves of Y-Phen, Y-CE and comparative molecule Y6 in Example 1 of the present invention;
[0058] Figure 6 This is a structural diagram of a perovskite solar cell prepared in Example 2 of the present invention;
[0059] Figure 7 The current-voltage curves of the perovskite solar cells using Y-Phen, Y-CE and the comparative molecule Y6 as the electron transport layer in Example 3 of the present invention respectively;
[0060] Figure 8 This is the certification report of the perovskite solar cell device using Y-CE as ETL in Example 3 of the present invention;
[0061] Fig. 9 The storage stability of the perovskite solar cell at 65 degrees in Example 3 of the present invention;
[0062] Fig.10 The stability of the perovskite solar cell described in Example 3 of the present invention under the condition of maximum power output at 45 degrees. DETAILED DESCRIPTION
[0063] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0064] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the art can be used. The raw materials or instruments used are all conventional products that can be obtained commercially, including but not limited to the raw materials or instruments used in the examples of this application.
[0065] In this embodiment, the Y6 molecule used was purchased and its structural formula is:
[0066]
[0067] Example 1: Preparation of non-fullerene acceptors (NFAs) Y-Phen and Y-CE materials
[0068] The synthetic route of Y-Phen is as follows:
[0069]
[0070] Compound M2 (11,12-bis(2-octyldodecyl)-3,8-heneicosyl-11,12-dihydrothieno[2”,3”:4’,5’]thieno[2’,3’:4,5]pyrrolo[3,2-g]thieno[2’,3’:4,5]thieno[3,2-b]indole-5,6-diamine, hereinafter referred to as M2) was synthesized by reacting the Y intermediate core M1 (12,13-bis(2-octyldodecyl)-3,8-heneicosyl-11,12-dihydrothieno[2”,3”:4’,5’]thieno[2’,3’:4,5]pyrrolo[3,2-g]thieno[2’,3’:4,5]thieno[3,2-b]indole-5,6-diamine) with the following steps: )-3,9-heneicosyl-12,13-dihydro-[1,2,5]thiadiazo[3,4-e]thieno[2”,3”:4',5']thieno[2',3':4,5]pyrrolo[3,2-g]thieno[2',3':4,5]thieno[3,2-b]indole, hereinafter referred to as M1) was dissolved in ultra-dry solvent tetrahydrofuran and added into a double-necked round-bottom flask under nitrogen protection, and then the reducing agent LiAlH 4 THF solution, M1 and LiAlH 4 The molar ratio of is 8.5:1, continue stirring for 7.5 minutes, and then reflux in an oil bath for 12 hours. Stop heating, cool to 0°C in an ice bath, slowly add an equal volume of water to the reaction system, stir evenly, and extract with ethyl acetate. Dry the organic phase with anhydrous sodium sulfate for 3.5 hours. Remove the solvent by rotary evaporation to obtain the M2 intermediate, which is used directly in the next step without purification.
[0071] Synthesis of compound M3 (10,11-bis(2-octyldodecyl)-7,14-heneicosyl-10,11-dihydrodipyrido[3,2-a:2',3'-c]thieno[2",3":4',5']thieno[2',3':4,5]pyrrolo[3,2-h]thieno[2",3":4',5']thieno[2',3':4,5]pyrrolo[2,3-j]benzopyrazine, hereinafter referred to as M3): M2 was dissolved in a mixed solvent of anhydrous ethanol and acetic acid in a volume ratio of 1:1, and 1,10-phenanthroline-5.6-dione was added, and the molar ratio of M2 to 1,10-phenanthroline-5.6-dione was 1:1.5. The reaction was carried out at 100°C for 9.5 hours. After cooling to room temperature, extraction was performed with water and ethyl acetate. The organic phase was dried over anhydrous sodium sulfate for 3.5 hours. The solvent was removed by rotary evaporation, and the crude product was purified by column chromatography to obtain intermediate M3;
[0072] Synthesis of compound M4 (10,11-bis(2-octyldodecyl)-7,14-heneicosyl-10,11-dihydrodipyrido[3,2-a:2',3'-c]thieno[2",3":4',5']thieno[2',3':4,5]pyrrolo[3,2-h]thieno[2",3":4',5']thieno[2',3':4,5]pyrrolo[2,3-j]benzopyrazine-8,13-dicarbaldehyde, hereinafter referred to as M4): Under nitrogen protection, M3 was dissolved in 1,2-dichloroethane and cooled to 0°C. After stirring for 20 minutes, DMF and POCl were added. 3 , M3, DMF and POCl 3 The ratio is 0.157mmol:0.55mL:2mmol. Reflux reaction for 12 hours. Then cool to room temperature, add sodium acetate aqueous solution, and continue stirring for 1 hour. The reaction system is extracted with dichloromethane, and the organic phase is dried with anhydrous sodium sulfate for 2 to 5 hours. The crude product is column chromatographed to obtain intermediate M4.
[0073] Synthesis of compound Y-Phen: Dissolve M4 and IC terminal raw materials in toluene, the ratio of M4 and IC terminal is 1:2.6. Then add BF 3 ·OEt 2 and acetic anhydride (volume ratio 3:1), stirred at room temperature for 38 minutes. Methanol was added dropwise while stirring the reaction solution to obtain a large amount of black precipitated solid Y-Phen. The nuclear magnetic hydrogen spectrum of the Y-Phen molecule is as follows Figure 1 shown.
[0074] The synthetic route of Y-CE is as follows:
[0075]
[0076] Synthesis of M9 (26,27-bis(2-hexyldecyl)-3,23-heneicosyl-6a,8,9,11,12,14,15,17,18,19a,26,27-dodecahydro-[1,4,7,10,13]pentaoxacyclopentadecano[2,3-i]thieno[2”,3”:4',5']thieno[2',3':4,5]pyrrolo[3,2-a]thieno[2”,3”:4',5']thieno[2’,3’:4,5]pyrrolo[2,3-c]benzopyrazine, hereinafter referred to as M9) )-3,8-heneicosyl-11,12-dihydrothieno[2”,3”:4’,5’]thieno[2’,3’:4,5]pyrrolo[3,2-g]thieno[2’,3’:4,5]thieno[3,2-b]indole-5,6-dione, hereinafter referred to as M7) was dissolved in anhydrous ethanol, and then M8 (2,3,5,6,8,9,11,12,13a,17a-decahydrobenzo[b][1,4,7,10,13]pentaoxacyclopentadecan-15,16-diamine, hereinafter referred to as M8) was added, the molar ratio of M7 to M8 was 1:1.1, and the reaction was carried out at 110°C for 9 hours. Then cooled to room temperature. Extracted with water and ethyl acetate. The organic phase was dried over anhydrous sodium sulfate. The solvent was removed by rotary evaporation, and the crude product was subjected to column chromatography to obtain the M9 intermediate.
[0077] Synthesis of M10 (26,27-bis(2-hexyldecyl)-3,23-heneicosyl-6a,8,9,11,12,14,15,17,18,19a,26,27-dodecahydro-[1,4,7,10,13]pentaoxacyclopentadecano[2,3-i]thieno[2”,3”:4',5']thieno[2',3':4,5]pyrrolo[3,2-a]thieno[2”,3”:4',5']thieno[2’,3’:4,5]pyrrolo[2,3-c]benzopyrazine-2,24-dicarbaldehyde, hereinafter referred to as M10) compound: Under nitrogen protection, M9 was dissolved in 1,2-dichloroethane and cooled to 0°C. After stirring for 20 minutes, DMF and POCl were added. 3 , M3, DMF and POCl 3 , M9, DMF and POCl 3 The ratio is 0.157mmol:0.55mL:2mmol, and the reaction is refluxed for 12 hours. Then the mixture is cooled to room temperature, and sodium acetate aqueous solution is added, and stirring is continued for 1 hour. The reaction system is extracted with dichloromethane, and the organic phase is dried with anhydrous sodium sulfate for 3.5 hours. The crude product is subjected to column chromatography to obtain intermediate M10.
[0078] Synthesis of compound Y-CE: Dissolve M10 and IC terminal raw materials in toluene, the ratio of M10 to IC terminal is 1:2.6. Then add BF3 ·OEt 2 and acetic anhydride (volume ratio 3:1), stirred at room temperature for 38 minutes, methanol was added dropwise while stirring the reaction solution to obtain a large amount of black precipitated solid, that is, compound Y-CE having the structure shown in formula II. The nuclear magnetic hydrogen spectrum of the Y-CE molecule is as follows Figure 2 shown.
[0079] The performance of the synthesized Y-Phen and Y-CE was compared with that of the comparative molecule Y6. The thermogravimetric analysis spectra and UV-visible-near infrared absorption curves are shown in Figure 2. Figure 3 and Figure 4 As shown in the figure, the electron mobility analysis curve is as follows Figure 5 The above results show that Y-Phen, Y-CE and Y6 have good thermal stability, reaching above 200°C; Y-Phen, Y-CE and Y6 have obvious near-infrared absorption properties; among them, the electron mobility of Y-Phen and Y-CE films is higher than that of Y6 molecules.
[0080] Example 2: Preparation of perovskite solar cell devices with Y-Phen and Y-CE as ETL
[0081] The Y-Phen and Y-CE materials prepared in Example 1 were respectively used as ETL perovskite solar cell devices, and the specific preparation methods were as follows:
[0082] The pre-patterned ITO glass substrate was ultrasonically cleaned with detergent, deionized water, acetone, and isopropanol for 15 min each. Subsequently, the cleaned ITO glass substrate was dried in an oven at 80 °C for 24 h and quenched with O before use. 2 The plasma treatment was carried out for 30 minutes. Then, CbzNaph SAM (1.5 mg / mL) was spin-coated on the ITO glass substrate at 3000 rpm for 30 seconds and annealed at 100 °C for 10 minutes. 2 and CsI were dissolved in DMF:DMSO solvent (volume ratio 4:1) to prepare a 1.4 M perovskite precursor solution with the formula of FA 0.95 Cs 0.05 PbI 3 (FAI, PbI 2 30 minutes before film deposition, 32.27 mg PbI was added to 1 mL of the solution. 2 、11.67mgPbCl 2, 9.38mg MACl and 1mg pF-PEAI. 40uL of perovskite precursor solution was spin coated at 5000 rpm for 50 seconds, and 180uL of chlorobenzene antisolvent was added to the center of the wet film 5 seconds before the end of the process. It was then annealed at 100°C for 30 minutes. Subsequently, PI solution (0.3mg / mL, dissolved in IPA) was spin coated on the prepared perovskite at 3000 rpm for 30 seconds and annealed at 100°C for 10 minutes. NFAs (Y-Phen or Y-CE) were weighed under ambient conditions, dissolved in chlorobenzene solvent (NFAs dissolved at a concentration of 10mg / mL), and heated at N 2 The solution was cooled to room temperature and spin-coated on the perovskite film at 3000 rpm for 30 s. All spin-coating processes were performed under N 2 The glove box was filled with O 2 and H 2 The O content was less than 5 ppm and the temperature was controlled at about 20°C. Finally, the metal mask (aperture area 0.04 cm 2 ) in a high vacuum chamber (<2×10 -6 torr) by thermal evaporation of 6 nm BCP and 100 nm Ag, and then thermal evaporation of 100 nm MgF on the glass side of the device. 2 As an anti-reflection layer, a perovskite solar cell is obtained, and its structure is shown in the figure Figure 6 shown.
[0083] Comparative Example 1: Perovskite solar cell device with Y6 as ETL
[0084] A perovskite solar cell device with Y6 as ETL was prepared. The preparation method was the same as in Example 2, except that the NFAs were Y6 materials and the concentration of Y6 was 10 mg / mL.
[0085] Experimental Example 1: Performance Verification
[0086] In a nitrogen-filled glove box, a AAA-class solar simulator (AM 1.5G, 100 mW cm -2 ) irradiated the prepared organic solar cell under the optimal conditions of the device (test area is 0.0289cm 2 ) to test the voltage-current curve, and the parameters are shown in Table 1. The current-voltage curve is shown in Figure 7 shown.
[0087] Table 1
[0088] ETL Layer Open circuit voltage Voc(V) Filling factor FF(%) <![CDATA[Short-circuit current density (mA cm -2 )]]> Light conversion efficiency (%) Y6 1.146 81.09 25.38 23.58 Y-Phen 1.168 84.27 25.42 25.03 Y-CE 1.176 85.41 25.50 25.61
[0089] As can be seen from Table 1, using Y-Phen and Y-CE as ETL of perovskite solar cells can achieve laboratory power conversion efficiencies of 25.03% and 25.61%, among which the device using Y-CE as ETL achieved a certified power conversion efficiency of 25.59%. These results are significantly higher than the power conversion efficiency of the device when Y6 is used as ETL (23.58%).
[0090] In addition, the optimized device with Y-Phen or Y-CE as the electron transport layer was placed in a nitrogen atmosphere glove box and continuously heated on a hot stage at 65°C. After 1440 hours, the PCE decay was less than 10%, which showed excellent performance in the preparation of perovskite solar cells. However, the PCE decay of the device with Y6 as the electron transport layer exceeded 20%.
[0091] The Y-CE prepared above was sent to a third party as ETL's perovskite solar cell device for efficiency verification, and a certified power conversion efficiency of 25.59% was obtained ( Figure 8 ).
[0092] Y6, Y-Phen and Y-CE as ETL processed perovskite solar cell devices in N 2 The efficiency trend of the device was tracked under the conditions of 65℃ storage in the glove box or 45℃ with one sun intensity at maximum power output. The results show that under the conditions of 65℃ storage ( Fig. 9 ) or at 45℃ with one sun at maximum power output ( Fig.10 )The device stability of Y-Phen and Y-CE is better than that of Y6.
[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A Y-type receptor material, characterized in that: It has a structure shown in any one of formulas Ⅰ to Ⅱ: Wherein, R1 and R2 are independently one of C6-C50 straight chain or branched chain alkyl groups; W, X, Y, and Z are independently one of hydrogen, fluorine, chlorine, bromine, and iodine.
2. The Y-type receptor material according to claim 1, characterized in that R1 and R2 are independently one of C6-C20 straight chain or branched chain alkyl groups.
3. The Y-type receptor material according to claim 1, characterized in that Select one of the following structures:
4. The method for preparing the Y-type receptor material according to claim 1, characterized in that: include: (1) Compound M1 reacts with LiAlH4 to obtain intermediate M2; (2) intermediate M2 reacts with 1,10-phenanthroline-5,6-dione to obtain intermediate M3; (3) intermediate M3, DMF, and POCl3 react to obtain intermediate M4; (4) The intermediate M4 reacts with the terminal group of IC to obtain a structure as shown in Formula I; The reaction process is: wherein R1, R2, W, X, Y, and Z are as defined in any one of claims 1 to 2.
5. The method for preparing the Y-type receptor material according to claim 1, characterized in that: include: (1) Compounds M7 and M8 react to obtain intermediate M9; (2) intermediate M9, DMF, and POCl3 react to obtain intermediate M10; (3) The intermediate M10 reacts with the IC terminal group to obtain a structure as shown in Formula II; The reaction process is: wherein R1, R2, W, X, Y, and Z are as defined in any one of claims 1 to 2.
6. Use of the Y-type acceptor material according to claim 1 in the preparation of perovskite solar cells.
7. A perovskite solar cell comprising a substrate, a bottom electrode, a hole transport layer, a perovskite photovoltaic active layer, an electron transport layer, and a top electrode; in, The electron transport layer comprises the Y-type acceptor material according to any one of claims 1 to 3.
8. A method for preparing a perovskite solar cell according to claim 7, characterized in that: include: The bottom electrode, hole transport layer, perovskite photovoltaic active layer, electron transport layer and top electrode are arranged in sequence on the substrate.
9. The preparation method according to claim 8, characterized in that: include: providing a substrate; A bottom electrode layer is formed on one surface of the substrate, a hole transport layer is formed on the side of the bottom electrode layer facing away from the substrate, a perovskite photovoltaic active layer is formed on the side of the hole transport layer facing away from the substrate, and an electron transport layer is formed on the side of the perovskite photovoltaic active layer facing away from the substrate.
10. The preparation method according to claim 9, characterized in that: In the electron transport layer, the Y-type acceptor material is dissolved in a solvent and spin-coated on the perovskite photovoltaic active layer. The concentration of the Y-type acceptor material is 2-20 mg / mL, preferably 10 mg / mL.
Citation Information
Patent Citations
Organic small molecule photovoltaic material based on benzopyrazine donor core and preparation method and application thereof
CN114181229A
Receptor material as well as synthesis method and application thereof
CN116063321A
Bimolecular coupling organic compound and application thereof in organic electronic device
CN118619975A
Cited By
Metal type coordination additive material as well as preparation method and application thereof
CN121378297A